The Incidence of Splenic Injury Following Blunt Abdominal Trauma (BAT), Sultan Qaboos University Hospital Experience - Al-Busaidi, Abdullah; Al-Shafei, Tariq; Al-Moqbali, Huda; Al-Kindi, Sara; Al-Saadi, Mohammed; Al-Busaidi, Nadya; Al-Qadhi, Hani (Scientific Research, 2017)
The aim of the study was to review traumatic splenic injury following blunt abdominal trauma (BAT), during the period from January 2009 to January 2015 at SQUH. The data for this study was retrospectively collected. It included 768 patients admitted to SQUH general surgery department following BAT. 43 patients with splenic injury were identified (34 males, 9 females). The mean age of patients with splenic injury was 36.0 years (34.4 years for males, 42.1 years for females). The most common mechanism of injury was motor vehicle collision (90.7%). Grade I, II are the most common grades of splenic injury. Non-Omani patients accounted for (51.2%) and most of them were pedestrians at the time of trauma. Ribs fracture is the most common injury associated with splenic injury. 36 (83.7%) patients were managed conservatively and 7 (16.3%) patients were splenectomized. Angioembolization was done for 11 (30.6%) patients. Despite the small population of Oman, high incidence of motor vehicle collision (MVC) increases the incidence of splenic injury among young age group.
Keywords: Spleen; Splenic Injury; Blunt Abdominal Trauma; Motor Vehicle Collision